Cloning and characterization of the CarbcL gene related to chlorophyll in pepper (Capsicum annuum L.) under fruit shade stress - Wang, Shu-Bin; Tian, Shi-Lin; Shah, Syed N. M.; Pan, Bao-Gui; Diao, Wei-Ping; Gong, Zhen-Hui (Frontiers in Plant Science, 2015)
Light is an important environmental factor during fruit development and ripening in pepper. Bagging is a significant agrotechnology for the illumination regulation of fruits; some previous researches had showed that bagging could improve the appearance and external quality of fruits and cause them to mature early. However, it would decrease the intrinsic qualities of fruits; especially, fruit bagging could decrease the content of capsanthin in peppers. Based on above-mentioned results, fruit bagging was used as the method of fruits shade stress in the experiment to explore the characteristics and molecular mechanisms of pepper fruits color change under shade stress. By using cDNA-AFLP under fruits shading, a fragment related to fruit color was obtained. Next, the full-length coding sequence of the gene was cloned from the fruits of pepper. Homologous gene alignment confirmed that the gene has high homology with the rbcL gene, named CarbcL. The function of the CarbcL gene was identified through virus-induced gene silencing (VIGS), it was found that the fruit color changed completely from green to red except for some residue of green fleck when CarbcL gene was silenced, and the green color of fruits had not fully faded in the control group and the empty vector group. Combination of determining the content of chlorophyll, it showed that CarbcL was involved in the metabolic control of chlorophyll in pepper fruits; subsequently, HPLC was used to determine the content of capsanthin in pepper fruit which CarbcL gene silencing, and it was also found that the content of capsanthin decreased sharply. These results further confirmed that CarbcL involved in the adjustment of chlorophyll and capsanthin.